2015
DOI: 10.1037/pne0000034
|View full text |Cite
|
Sign up to set email alerts
|

Dominant right hemisphere controls biased rotation perception.

Abstract: Bistable perception is a form of visual illusion that is widely used in the context of brain research. The spinning dancer illusion is a form of bistable perception that can be used to study the perception of motion and rotation. However, the underlying mechanism of such bistability is not fully understood. To determine the possible mechanisms involved, psychophysical methods may provide valuable tools. In the present study, we investigated the effects of stimulus position in the visual field on the duration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Moreover, a larger number of figures were interpreted as spinning CW in the LVF than in the RVF (corresponding to the fact that participants interpreted a larger number of figures as right-limbed in the RVF rather than in the LVF in the inward-rotation condition, and a larger number of figures as right-limbed in the LVF rather than in the RVF in the outward-rotation condition). These results are consistent with those reported by Alipour and Kazemi [24], who found analogous effects by presenting the spinning dancer illusion in the two hemifields. With the exception of that study, no previous research examined the effects of eccentricity on the perception of the spinning direction of bistable stimuli.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, a larger number of figures were interpreted as spinning CW in the LVF than in the RVF (corresponding to the fact that participants interpreted a larger number of figures as right-limbed in the RVF rather than in the LVF in the inward-rotation condition, and a larger number of figures as right-limbed in the LVF rather than in the RVF in the outward-rotation condition). These results are consistent with those reported by Alipour and Kazemi [24], who found analogous effects by presenting the spinning dancer illusion in the two hemifields. With the exception of that study, no previous research examined the effects of eccentricity on the perception of the spinning direction of bistable stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is some evidence suggesting that the hemifield of presentation might also affect the perceived spinning direction of ambiguous stimuli for other, non-motoric, reasons. In particular, as already proposed by [24], the usual experience of optic flow (i.e., the motion patterns of objects in the visual field of the observer; [25,26]) could induce hemispheric-specific rotational biases when one observes rotating objects with an ambiguous spinning direction. Indeed, the experience of optic flow (which occurs during walking, running, driving, and other activities implying a forward motion) is represented by the constant movement of objects "toward" the observer, but is also analogous to the perception of the motion vectors on the visible surface of a cylinder rotating CW (clockwise) in the LVF, and of those on the visible surface of a cylinder rotating CCW (counterclockwise) in the RVF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetrical biases like these have also been reported in the perception of bistable motion stimuli. Both Alipour & Kazemi (2015) and Lucafò et al (2021) demonstrated that ambiguously rotating human silhouettes are more likely to be perceived as rotating clockwise when presented to the left visual field. Researchers in both studies suggested that processes underlying optic flow (the movement of objects across the visual field during forwards locomotion) may help to explain this result however, no corresponding bias for counterclockwise rotation was found for the right visual field in either study and, furthermore, it is unknown whether this effect generalises to other similar motion animations (e.g.…”
Section: Spatial Precision and Other Differences Across The Visual Fieldmentioning
confidence: 99%
“…However, the aims of these studies were never directed at understanding the influence of spatial differences on priors and their effect on awareness. Rather, they were focussed on other interesting phenomena such as hemispheric asymmetry (Alipour & Kazemi, 2015;Lucafò et al, 2021), idiosyncratic differences in spatial biases for higher order object categories (Afraz et al, 2010;Finlayson et al, 2020), and visual pattern persistence (Breitmeyer & Ritter, 1986;Rutherford, 2003).…”
Section: Spatial Precision and Other Differences Across The Visual Fieldmentioning
confidence: 99%